The quadratic equation is;
![\begin{gathered} y\text{ = -}(x^2)/(2)\text{ - x + 5} \\ \\ \text{where a = -}(1)/(2)\text{ , b = -1 and c = 5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gp4uhezkknqj9z6sbe7r0w0trkit8n2knj.png)
Here, given the information in the question, we want to write the quadratic equation in its standard form
To do this we shall make some substitutions;
The maximum point of the quadratic equation is also called the vertex
In this question, the vertex is g(-1) = 6
So this is (-1,6)
The other point is g(-3) = 4
So the point here is (-3,4)
Thus, we have a quadratic equation with vertex (-1,6) that passes through the point (-3,4)
The general equation for a quadratic equation having a vertex and passing through a given point is;
![y=a(x-h)^2\text{ + k}](https://img.qammunity.org/2023/formulas/mathematics/college/2wt4iqy6y92ugda1burxjci7twjy8ps9zq.png)
where (h,k) represents the coordinates of the vertex and (x,y) represents the coordinates of the points that the quadratic equation passes through
Thus, we have;
![y=a(x+1)^2\text{ + 6}](https://img.qammunity.org/2023/formulas/mathematics/college/gcv8ffs3e0xjwgn062tcslh5wad3p9t39d.png)
so to get the a value in this form, we substitute the values of the points; where x is -3 and y is 4
We have;
![\begin{gathered} 4=a(-3+1)^2\text{ + 6} \\ \\ 4\text{ = 4a + 6} \\ 4a\text{ = 4-6} \\ 4a\text{ = -2} \\ \\ a\text{ = }(-2)/(4) \\ \\ a\text{ = }(-1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/40kn729hhi2mlryka9o1d6py04n5qyltdp.png)
So the quadratic equation can be written as;
![y\text{ = }(-1)/(2)(x+1)^2\text{ + 6}](https://img.qammunity.org/2023/formulas/mathematics/college/vuozvooh1ovcsbq2gel4wuinospd4i28f1.png)
We can rewrite this in the form in the question as follows;
![\begin{gathered} y\text{ = }(-1)/(2)(x+1)^2\text{ + 6} \\ \\ y\text{ = }\frac{-1(x^2\text{ + 2x + 2) }}{2}\text{ + 6} \\ \\ y\text{ = -}(x^2)/(2)\text{ - }(2x)/(2)\text{ - }(2)/(2)\text{ + 6} \\ \\ y\text{ = -}(x^2)/(2)\text{ - x -1 + 6} \\ \\ y\text{ = -}(x^2)/(2)\text{ - x + 5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nk23bfusq1bd9c5g6u1ef9lwcazfgmk49a.png)